Compressive Behaviour Of Syntactic Foam Filled With Epoxy Hollow Spheres Having Different Wall Thickness. - M. Ariff, Z; Samsudin, S.S.; A. Mutalib, N.A. (2010)

(untitled)
An innovative approach of producing epoxy syntactic foams was developed by incorporating single-coated and double-coated of epoxy hollow spheres within epoxy resin matrix.